Peran Ulama Dalam Mitigasi Pandemi Covid-19 - Zahratunnisa Zahratunnisa (ADALAH, 2020)
Abstract:The Covid-19 pandemic has had a complex frustrating impact on society. Da'wah opportunities to encourage mitigation of major outbreaks given the nature of religion which enters all fields. The description of the qualitative socio-religious analysis from this paper aims to find the position of the ulama in a pandemic situation from an Islamic perspective, as well as the significance of da'wah in the maximum mitigation of the outbreak. Where it is found here that ulama are part of ulil amri who are fully responsible whether or not there are other ulil amri elements. The method of da'wah which is significant in mitigating a pandemic is by combining a religious basis and a scientific basis to convince the public, in addition to persuasive patterns along with structured real efforts and exemplary which is always put forward.Keywords: Pandemic; Mitigation; Scholars Abstrak:Pandemi Covid-19 memberi dampak frustasi kompleks di masyarakat. Peluang dakwah untuk mendorong mitigasi wabah besar mengingat watak agama yang masuk ke semua bidang. Deskripsi analisa kualitatif sosio religi dari tulisan ini bertujuan menemukan posisi ulama dalam situasi pandemi dalam pandangan keislaman, serta signifikansi dakwah dalam mitigasi maksimal wabah. Dimana ditemukan disini bahwa ulama adalah bagian dari ulil amri yang bertanggung jawab penuh baik dengan ada atau tidak adanya unsur ulil amri yang lain. Adapun metode dakwah yang signifikan dalam mitigasi pandemi adalah dengan menggabungkan dasar keagamaan dan dasar saintifik untuk meyakinkan masyarakat, di samping pola persuasif beserta upaya riil terstruktur dan juga keteladanan yang selalu dikedepankan.Kata Kunci: Ulama;  Mitigasi;  Pandemi